Two new small flowered Cyrtochilum species (Orchidaceae: Oncidiinae) from Venezuela - Morillo, Gilberto; Dalström, Stig (Lankesteriana: International Journal on Orchidology, 2013)
During ongoing research on the genus Cyrtochilum Kunth in the Venezuelan Andes, two new species have been found, which are described, illustrated and compared with similar species here.